Analysis of Cultural Background Variables and Cultural Biases in Counseling - Roza, Yulia; Silvianetri, Silvianetri; Kamran, Syed Ali; Butt, Muqaddas Shah (Yayasan Minang Darussalam, 2022)
The background of this research is the lack of attention to the variables in the cultural background of counselors and clients in a counseling process. In fact, variables such as beliefs or religion, values, norms, traditions, and language have a crucial role in counseling. This research uses a systematic literature study approach with data collected from various sources consisting of books, journals, research reports, and articles on cultural background and cultural bias in counseling. Reference data is sorted by periodization, keywords, and limitations. This study aims to analyze the cultural background variables and cultural biases involved in the counseling process. The results of this study are expected to help counselors to create effective communication in the counseling process and achieve counseling goals.